Translation Errors and Their Causes in Indonesian to English Translations by Junior High School Students - Dohra Fitrisia; Chairina Nasir; Tilka Billah Attaqwi (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
This research focused on analyzing the error types and error causes made by ninth-grade students of SMP Negeri 3 Ingin Jaya in translating Indonesian into English sentences. This study used purposive sampling technique which consists of 32 students from class IX.1. The instruments of this qualitative study are translation test and interview. The researcher determined the types of errors using the Surface strategy taxonomy proposed by Dulay et al. (1982) and An-Nisa Suroso (2021) which consists of omission, addition, misordering, and misformation. To determine the causes of translation errors made by the students, the researcher used the theory proposed by Norrish (1987) and Sari (2019); carelessness, first language interference, and translation. The findings show there are 276 errors occurred in the students’ translation test and calculated a total of 127 items of misformation errors (46.01%), then 92 items errors of omission (33.33%), 34 items error of addition (12.31%), and 23 items of errors of misordering (8.33%). Carelessness, first language interference, translation, lack of vocabulary, and low self-confidence were the students’ causes of errors.